PENGARUH MODEL PEMBELAJARAN SELF REGULATED LEARNING TERHADAP KECERDASAN EMOSIONAL DAN HASIL BELAJAR BIOLOGI PESERTA DIDIK KELAS X SMA NEGERI 8 DENPASAR - I Wayan Suanda; Kadek Yuniari Suryatini; A.A. Istri Mirah Dharmadewi; Ronaldus Marsi (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This study aims to determine the effect of the self regulated learning model on emotional intelligence and biology learning outcomes of class X students of SMA Negeri 8 Denpasar. The population in this study were all class X MIA students of SMA Negeri 8 Denpasar consisting of 7 classes. Sampling used a random sampling technique, where class X MIA 7 was the experimental class and class X MIA 5 was the control class. Emotional intelligence data and student learning outcomes data were obtained using an essay test method and analyzed using a t-test. Based on the analysis of the hypothesis testing of emotional intelligence data and student learning outcomes data with a t-test, a significance figure of 0.00 was obtained with a significance level of 5%. This shows that the examiner's significance figure <the set significance figure (0.00 <0.05) so Ho is rejected and Ha is accepted. Based on the results of the study, it is known that the self regulated learning model affects emotional intelligence and biology learning outcomes of class X students of SMA Negeri 8 Denpasar.